Using multiple objectives in participatory assessment of International Livestock Research: lessons learned - Kristjanson, Patricia M.; Randolph, Thomas F.; Thornton, Philip K.; Reid, Robin S.; Ryan, J. (CAB International, 2009)
This chapter describes a systematic quantitative research priority assessment exercise undertaken with the involvement of roughly 100 researchers and partners of the International Livestock Research Institute (ILRI) in 1999 for an array of research alternatives, as part of the development of a new Institute strategy. It describes the criteria employed for the economic, environmental, poverty, geographic and capacity-related impacts of a wide range of research themes. Lessons learned in applying such a framework and the challenges related to evaluating each criterion are discussed. Subsequently, the influences of recommendations arising from the exercise are explored, so as to appraise contributions to the evolution of ILRI’s research focus and approach during the 10-year period since the priority assessment exercise was completed.